1996
DOI: 10.1002/bbpc.19961001220
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed EPR experiments on radical pairs in photosynthesis: Comparison of the donor‐acceptor distances in photosystem I and bacterial reaction centers

Abstract: Pulsed EPR spectroscopy is applied to the radical pairs P&Q, in bacterial reaction centers of Rhodobacter sphaeroides R-26 and P;&, ' in photosystem I from Synechococcus elongatus. For both radical pairs an outof-phase echo was observed showing a deep modulation as a function of the spacing between the two microwave pulses. From the modulation frequency the dipolar and isotropic couplings between the radical pair spins were derived. For the bacterial reaction centers a dipolar coupling of D = -121 FT was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 14 publications
7
53
1
Order By: Relevance
“…The distance from the centre of P700 to the centre of this structure is 25 (AE1) A Ê , in excellent agreement with the 25.4 (AE0.3) A Ê determined by EPR (Zech et al, 1996;Dzuba et al, 1997;.…”
Section: Secondary Electron Acceptorsupporting
confidence: 66%
“…The distance from the centre of P700 to the centre of this structure is 25 (AE1) A Ê , in excellent agreement with the 25.4 (AE0.3) A Ê determined by EPR (Zech et al, 1996;Dzuba et al, 1997;.…”
Section: Secondary Electron Acceptorsupporting
confidence: 66%
“…In both samples, the isotropic exchange coupling is extremely weak, and only an upper limit of J Ͻ 1.0 Ϯ 0.8 T can be given. Using a simple point-dipole model, the measured dipolar coupling constant corresponds to a distance of 25.3 Ϯ 0.3 Å between P700 ϩ and A 1 Ϫ in the rubA mutant, which is the same within error as the distance of 25.4 Ϯ 0.3 Å established between P700 ϩ and A 1 Ϫ in several preparations of wild-type PS I (13,(23)(24)(25). Thus, the absence of the F X cluster does not influence the position and orientation of phylloquinone in the A 1 site.…”
Section: Electron-spin Echo Distance Measurements Of P700mentioning
confidence: 75%
“…[85,86] In this case, the echo is observed out-of-phase [87] and the method is therefore termed out-of-phase ESEEM (electron spin echo envelope modulation). It has been demonstrated that the pulse sequence (p/4)-s-(p)-s echo provides optimum signal.…”
Section: Other Experimentsmentioning
confidence: 99%